2007
DOI: 10.14723/tmrsj.32.603
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Heating of Thin Cu Film

Abstract: Thin Cu films with different thickness and microstructure were prepared using evaporation with a quartz substrate, followed by microwave irradiation in air (frequency of microwave:2.45 GHz, incident flux of microwave:563 W, irradiation time: 600 s). Microwave heating of thin Cu film is quite anomalous. The abrupt temperature rise and drop occur at early stage of microwave irradiation, then continuous temperature rise appears. The temperature change is caused by various combinations of the change in the rate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
(12 reference statements)
0
7
0
Order By: Relevance
“…Since reaction (2), that is, the formation of TiN, is exothermic, the larger the amount of TiN formed by microwave heating, the larger the amount of heat generated for the TiN reaction. As mentioned above, the formation of TiN was enhanced by microwave irradiation in N 2 gas and air.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since reaction (2), that is, the formation of TiN, is exothermic, the larger the amount of TiN formed by microwave heating, the larger the amount of heat generated for the TiN reaction. As mentioned above, the formation of TiN was enhanced by microwave irradiation in N 2 gas and air.…”
Section: Resultsmentioning
confidence: 99%
“…The authors reported that it is feasible to heat thin Au and Cu films by microwave irradiation. 1,2 On the other hand, Roy et al reported first in 1999 that compacted metal powders could be heated and sintered by microwave irradiation. 3 Recently, there has been much interest in the microwave heating of metal powders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, few applications have been conducted so far on heating metal bulk. 1 On the other hand, recently, there has been much interest in microwave heating of metal powders [2][3][4][5][6][7] and thin metal films, [8][9][10] which have large specific surface areas compared with metal bulk. Roy et al 2,3 reported that the microwave heating of a Cu powder compact sample is quite anomalous although the sample heats up very fast in both electrical and magnetic fields.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Yoshikawa et al 7 reported that Cu particles having diameters .2 mm are not heated well at the position of maximum magnetic field and are only heated by the occurrence of electrical discharge at the position of maximum electric field. The authors 10 previously reported that microwave heating of thin Cu film shows anomalous behaviour in which both peak and steady state temperatures appear during microwave irradiation. However, there have been few reports regarding microwave heating of metals, and also its heating behaviour is not well understood.…”
Section: Introductionmentioning
confidence: 99%